Mekanisme Pemungutan PBB-P2 pada Badan Pendapatan Daerah Kota Surabaya - Revi Donik Kalma (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
The Rural and Urban Land and Building Tax (PBB-P2) is a type of local tax that plays a crucial role in increasing Locally-Generated Revenue (PAD). The Surabaya City Regional Revenue Agency, as the authority responsible for local tax management, is tasked with effectively collecting PBB-P2 in accordance with applicable regulations. The objective of this final project is to examine and understand the PBB-P2 collection mechanism at the Surabaya City Regional Revenue Agency. The methods employed in compiling this project include observation, interviews, literature review, and documentation. The data used consists of primary data obtained through interviews with PBB collection officers and secondary data derived from relevant laws, regulations, documents, and official sources. The findings indicate that the PBB-P2 collection mechanism at the Surabaya City Regional Revenue Agency utilizes an official assessment system and is carried out through several stages: tax object registration, data collection, valuation of the Tax Object Sale Value (NJOP), determination of tax liability, issuance of the Tax Due Notification Letter (SPPT), payment, and collection. PBB-P2 payments can be made either directly or via digital services. However, implementation faces challenges such as low taxpayer awareness, tax arrears, economic factors, and unreported changes in tax object data. Efforts undertaken by the Surabaya City Regional Revenue Agency include public outreach, tax education, penalty waivers, verification of tax object data, and mobile tax service units. Thus, the PBB-P2 collection mechanism at the Surabaya City Regional Revenue Agency is implemented in a structured manner, in accordance with applicable regulations, to support the optimization of local tax revenue
:: Finalisasi file repositori 21 Juli 2026_Kurnadi
Keywords: PBB-P2; Regional Revenue Agency; Surabaya City